MEASURING PRODUCTION PERFORMANCE OF DIFFERENT PRODUCT MIXES IN SEMICONDUCTOR FABRICATION - Chung, Shu-Hsing; Pearn, Wen Lea; Lee, Amy (International Journal of Industrial Engineering: Theory, Applications and Practice, 2022)
In a competitive market. a company needs to fully utilize its current capacity in order to acquire higher profit. The purpose of this paper is to present an effective approach to fmd a set of product' mix efficient fOT the company to achieve the optimal production. Simulation is flIst used to generate the data of performance measures of different product mixes in a semiconductor fabricator. Data Envelopment Analysis (DEA) is applied next to measure multiple inputs and outputs, without pre-assigning weights, far product mixes, and an efficiency score for producing each product mix relative to other mixes can be obtained. The results provide guidance for a fab in accepting orders when its capacity cannot fully satisfy all the product demand.